Spontaneous rupture of the lens capsule in hypermature cataract: presentations and outcomes. Issue 8 (13th November 2015) - Goel, Neha; Nagar, Meena
Abstract : Aim: To describe the occurrence of spontaneous rupture of the lens capsule in patients with hypermature cataract. Study design: Consecutive case series. Methods: The records of patients with hypermature cataract and spontaneous capsular dehiscence seen and managed at a tertiary eye care centre between August 2012 and August 2014 were reviewed retrospectively. Results: 10 eyes of 10 patients were identified. Best-corrected visual acuity (BCVA) was limited to light perception in all patients. Three eyes had anterior dislocation of the nucleus, two had posterior dislocation and in five the nucleus was presumed to have absorbed. Eight eyes (80%) demonstrated both anterior and posterior capsular tears and five eyes (50%) showed calcification spots in the capsule remnants. Other features at presentation included corneal oedema (two eyes), vitritis (four eyes), raised intraocular pressure (one eye) and hypopyon (one eye). Removal of the nucleus through anterior (three eyes) or posterior route (two eyes) was carried out in all patients with dislocated nucleus. Intraocular lens could be implanted in seven eyes (70%) and they had a final BCVA ranging from 6/18 to 6/36. Conclusion: Spontaneous lens capsule rupture can occur in hypermature senile cataract (HMSC) and result in anterior or posterior dislocation of the nucleus or spontaneous resorption with or without an accompanying inflammatory reaction of varying severity. An acceptable visual outcome can be obtained, except in the presence of associated glaucoma or corneal decompensation.